If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x = 5x + 61 Reorder the terms: 6 + -6x = 61 + 5x Solving 6 + -6x = 61 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + -6x + -5x = 61 + 5x + -5x Combine like terms: -6x + -5x = -11x 6 + -11x = 61 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + -11x = 61 + 0 6 + -11x = 61 Add '-6' to each side of the equation. 6 + -6 + -11x = 61 + -6 Combine like terms: 6 + -6 = 0 0 + -11x = 61 + -6 -11x = 61 + -6 Combine like terms: 61 + -6 = 55 -11x = 55 Divide each side by '-11'. x = -5 Simplifying x = -5
| N-25=18 | | 2(3x-1)-6x=-4 | | 3x+4x+5=-3 | | N-25= | | 3(7x+7)=252 | | (W+1)(2w-3)=5 | | 5=3k-2k | | Log(x)=9 | | 3x+4x+5=3 | | D+4.7=2.8t(7.4) | | 6(7m+3)= | | 3x+4x-5=3 | | -0.2x(-0.07)= | | 9b=4b-25 | | 7x+1=8x+16 | | 1650-25h=1325 | | 6x-3x=-6+5x | | 5(x-7+4)=34 | | -20x-8+7=-5 | | .23=log(x) | | 3x-4x-5=3 | | y-7=(x+4) | | 2(x+4)+2(x)=4(x+2) | | 3x-4x+5=-3 | | 3b=10-b | | 5(3x+7)=35 | | 3*-5+12-5*-5=22 | | -12=-15x | | 3x+4x-5=-3 | | 7x+5=44-6x | | -11+9-y=4y+3 | | 5(3x+7)=72 |